2009
DOI: 10.1021/jz900146f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Epitaxial Registry on Graphite of a Series of Nanoporous Self-Assembled Molecular Monolayers

Abstract: We have analyzed by STM the detailed structures of a series of nanoporous honeycomb networks stabilized by alkyl chain interdigitation on graphite at the liquid−solid interface, that is, clip-like noncovalent bonding. The variations observed as a function of the length of the peripheral aliphatic chains show that the assembly is directed not only by lateral intermolecular interactions but also by the adsorption site on the substrate. We derive an atomically accurate model for the registry with graphite of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 35 publications
(44 reference statements)
4
58
0
Order By: Relevance
“…It has been well documented in the literature that the substrate lattice has a strong bearing on the self-assembly of molecules. [14,[61][62][63] The graphite lattice that is used as a substrate in the present study is built up of layers with a honeycomb arrangement of carbon atoms. The basal (001) plane of graphite has a threefold symmetry and the carbon atoms along the direction of any C 3 axis display the same zigzag extension as the zigzag skeleton of the carbon backbone of an all-trans alkyl chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented in the literature that the substrate lattice has a strong bearing on the self-assembly of molecules. [14,[61][62][63] The graphite lattice that is used as a substrate in the present study is built up of layers with a honeycomb arrangement of carbon atoms. The basal (001) plane of graphite has a threefold symmetry and the carbon atoms along the direction of any C 3 axis display the same zigzag extension as the zigzag skeleton of the carbon backbone of an all-trans alkyl chain.…”
Section: Resultsmentioning
confidence: 99%
“…The lattice match between alkyl chains and the graphite substrate has been confirmed widely. [51,[61][62][63] The lateral arrangement of alkyl chains on the graphite lattice is also governed by the similarity in the lattice parameters. Typically, it has been observed that the distance between unsubstituted alkanes within a lamella (along the lamella axis) is approximately 4.26 , which is in reasonable agreement with the distance between every other carbon row of the graphite lattice (4.24 ).…”
Section: Resultsmentioning
confidence: 99%
“…[21] Regarding the isotropic network, the TSB-3,5-C 12 tecton has been chosen because it can form a honeycomb network the pore diameter of which (1.9 nm) is commensurate with the size of the NCs (2 nm). [19] However, it has been reported that the tecton TSB-3,5-C 12 could self-assemble along various schemes depending on concentration and temperature. [19] At room temperature, below the critical concentration C C =10 -3 mol.L -1 , a honeycomb structure is formed ( Figure 1C 1 and 1C 2 ).…”
Section: -Results and Discussionmentioning
confidence: 99%
“…A specially flexible example is based on a functional unit comprising interdigitated alkyl chains forming a clip between neighbouring molecules [42]. Mo− lecular building blocks receiving three such "clips" forming 60°angles form a honeycomb structure on a graphite sub− strate with tunable pore size [45]. The molecular structure and the honeycomb network obtained is schematized in Fig.…”
Section: D Molecular Self Assembly For Dye Immobilizationmentioning
confidence: 99%